PERTANGGUNGJAWABAN PEMERINTAH TERHADAP CAGAR BIOSFER GIAM SIAK KECIL BUKIT BATU BERDASARKAN HUKUM LINGKUNGAN INTERNASIONAL - Ira Gesima Sirait; Firdaus '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Biosphere Reserves are ekosisem mainland and coastal or ocean or a combination of more than one type of ecosystem, which is internationally recognized as part of the Man And Biosphere (MAB) Programme of UNESCO in accordance with the legal framework. Biosphere Giam Siak small rocks were designated as a Biosphere Reserve in the 21st Session Session Of The International Coordinating Council Of theman And the biosphere is one of 22 locations nominations proposed by 17 countries. Biosphere Giam Siak Kecil-Bukit Batu has advantages as the largest peat swamp forests, but the management and protection of the region is very poor, it is proved by the destruction of the heritage area due to human activities that have an impact on air pollution and has been designated as a national disaster. Based on the above description, the problem can be formulated as follows: First, How is the implementation of the responsibilities undertaken by the government of the region of the biosphere reserve in accordance with international environmental law? Secondly, The extent to which the government's efforts in implementing Article 9 of the Seville Strategy 1995 on the network of biosphere reserves?This type of research can be classified into types of normative juridical, namely the study of the principles contained in the International and National Law. From the research, there are two main things that can be inferred. First, the Government has taken concrete steps in order to biosphere reserves, namely the presence of Riau Governor Decree No. Kpts. 920 / V / 2010 Date of May 14, 2010 on the establishment of the Management Coordination Agency GSK-BB Biosphere Reserve. The decision contains Coordination and its partnership between the manager who has an interest. Each party involved in the management team reserves giam siak biosefer small rock hill has roles and responsibilities of different but interrelated. However, the implementation, the Government did not carry out their roles and responsibilities to the maximum so that the biosphere reserve is damaged and bad. ; Secondly, Based on the mandate of the Seville strategy, if reserves were damaged and not functioning as it should, then the government has the responsibility to perform the restoration effort, however based on the data obtained, the government did not implement the program for reserve recovery seriously and quickly. Suggestions Author, First, management of funds (trust fund) that is transparent to carry out activities Coordinating and managing the reserve It needs a special Budget allocation for the management of biosphere reserves. Second, a special team should be formed outside the biosphere reserve of the existing government institutions, so as to maximize its performance and focused. If there should be rules regarding sanctions for a team that does not perform its responsibilities.Keywords: Biosphere - Responsibility - Strategy seville